The Effect of Special Exercises for developing Motor Speed of Armed arm in Epee in U20 Wheelchair Fencing - Fouad, Ali; Mahdi, Abdalhadi Hameed (Journal of Physical Education, 2022)
The research aimed at designing special exercises for developing motor speed in armed arm in epee for youth wheelchair fencers as well as to identify their effect on the subject. The researchers used the experimental method on (7) epeeist wheelchair fenders under twenty years old from the Iraqi national federation. The training sessions were supervised by the researchers including eight weeks for special preparation phase with three sessions per week making a total of 24 training session. Low and high intensity interval training was used with 65 – 90% intensity. The researchers used the main part of training for skill preparation. The data was collected and treated using SPSS to conclude that the subjects developed in motor speed in armed arm. The researchers recommended generalizing these exercises for preparing young and youth wheelchair fencers.